Supramolecular modification of a metal–organic framework increases sorption switching: insights into reversible structural deformation of ZIF-8. Issue 39 (20th September 2022) - Tiba, Al A.; Perman, Jason A.; MacGillivray, Leonard R.; Tivanski, Alexei V.
Abstract : Use of chemical modulators during the synthesis of coordination frameworks is an important strategy to affect and tune properties of porous materials. Abstract : Use of chemical modulators during the synthesis of coordination frameworks is an important strategy to affect and tune properties of porous materials. Herein, we introduce an approach to understanding structural modulation and deformation of porous nanocrystals in the context of gas adsorption by using atomic force microscopy (AFM) nanoindentation, scanning electron microscopy energy dispersive X-ray spectroscopy, and gas physisorption analysis. Modified nanocrystals of the prototypical zeolitic-imidazolate framework-8 (ZIF-8) were generated in triethylamine (Et3 N) via in situ supramolecular modification in solution phase and compared to unmodified nanocrystals. The crystals of both samples had similar rounded morphologies with identical sizes ranging from 30–140 nm in diameter and height of 30–90 nm. We demonstrate that using Et3 N as a modulator results in a conspicuous decrease in elastic modulus (0.7 ± 0.2 GPa) compared to unmodified nanocrystals of ZIF-8 (2.1 ± 0.8 GPa). Argon gas adsorption analysis also reveals that the more flexible, amine-modified framework exhibited gradual and cooperative gate-opening structural expansion at P / P 0 = 0.33 ± 0.02 compared to the steeper and stepwise characteristics of unmodified samples of ZIF-8 at P / P 0 = 0.45 ± 0.02. The lower Ar gas pressure required to induce reversible structural deformation during gas uptake corresponds to the decrease in elastic modulus of Et3 N-modified nanocrystals of ZIF-8. Structural characterization suggests that Et3 N contributed to lower relative numbers of hydrogen bonds and 2-methylimidazole linkers, creating more point defects in the modified framework while crystal structure remained unchanged. Our study also demonstrates how a combination of AFM nanoindentation, gas uptake, and spectroscopic characterization can be applied to understand structural and energetic changes upon adsorption in porous nanocrystals with modified supramolecular interactions.